ON THE EMANCIPATION IN THE CONTEMPORARY FAIRY TALE THE TREE OF LIES BY FRANCES HARDINGE (Journal of Contemporary Philology, 2021)
The paper titled On the emancipation in the contemporary fairy tale The Tree of Lies by Frances Hardingefollows the transformation of the female characters in the novel The Tree of Lies by the contemporary British writer Frances Hardinge. Beginning with the classical Gothic tropes and ending with contemporary emancipation, the paper analyzes the character’s attempts, through various strategies of resistance, to realize their freedom, desire for research, and self-definition. An analysis of the novel requires a theoretical background, which is supplied via the concepts of Richard Rorty and Emmanuel Levinas, particularly through their work on the responsibility for the Other, female solidarity, and consensus through conversation between female characters and their sub-community. Through the two key characters I will confront the position of authority that insists on metaphysical truths, absolute discipline and permanence versus, on the other hand, the position of resistance, escape from such authority, and struggle for progressand change in the emancipatory sense. The novel, through the opposing concepts of authoritarianism versus emancipation and progress, establishes a bridge and continuity of the struggle of the 19th century and the actuality of that struggle today, which gives it a special authenticity and conviction.
Keywords: emancipation; power; patriarchy; resistance; solidarity; subversion